persepsi konsumen Terhadap kualitas produk dan pelayanan es krim angi - Dina, Felesia; Artanti, Felicia Tania; Felycia, Stefanie; Steven, Ciu; Effendy, Dudy; Gery, Gregorius Seto Mariyanto (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to determine: (1) Consumer perceptions of the quality of Angi’s Ice Cream products; and (2) Consumerperceptions of the service quality of Angi’s Ice Cream. This type of research is descriptive research with quantitative researchmethods and a survey approach via Google Forms. The research population was 40 Angi’s Ice Cream consumers, who werealso the samples in this study. By applying this research method, the researcher distributed questionnaires to 40 respondents byGoogle form. Data analysis techniques used descriptive statistical analysis. The results showed that (1) Consumer perceptionsof the quality of Angi's Ice Cream products were good, and (2) Consumer perceptions of the service quality of Angi's Ice Creamwere also good. This was concluded based on the results of a survey on the analysis of "Consumer Perceptions of the Quality ofAngi’s Ice Cream Products and Services"